Men of Shoubra: Hairdressing, shades of masculinities, and ghosts of sectarianism - Mohmed, Tarek Moustafa (AUC Knowledge Fountain, 2018)
This thesis looks at the intersections of masculinities, religiosity, and Coptic-Muslim cohabitation/ tensions through exploring the everyday lives of Shoubra’s male hairdressers who work exclusively with women. It builds on the fieldwork that I had conducted as an assistant hairdresser for one of Shoubra’s Coptic hairdressers. The thesis argues that the interplay of masculinities and religious identities is strongly embedded in the everydayness of Shoubra as a social space in ways that make them inseparable. This project started as an attempt to look at the masculinities of male hairdressers whose clients are women; however, by time it turned to be a project that aimed at unpacking and challenging categories such as Muslims, Copts, and masculinities. This unpacking was premised on embedding such categories in the multi-layered social and political structures of Shoubra in order to understand how the intersections between masculinities and religious identities shape the gendered relations between the male hairdressers and their women clients.